Analisis Aspek Struktural dan Nonstruktural dalam Novel Sang Pemimpi Karya Andrea Hirata - Setio Elisa (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2021)
Analysis of Structural and Non-Structural Aspects in Andrea Hirata's Novel the Dreamer. The aims of the research are 1) To describe the intrinsic elements of the novel Sang Pe dreamer by Andrea Hirata. 2) Describe the extrinsic elements of the novel Sang Pe dreamer by Andrea Hirata. 3) Describing the values contained in the novel The Dreamer by Andrea Hirata. The research method used to analyze the structural and non-structural aspects is descriptive qualitative. Descriptive approach with content analysis techniques in the preparation of work steps. The sampling technique used was purposive sampling. Data collection techniques using reading and note-taking techniques. The data analysis technique uses flow model of analysis. The conclusion of this research, that is (1) The novel The Dreamer has a complete structure, consisting of themes, plots. Characterization, point of view, and setting. (2) There are four elements in the relationship between the elements of the novel Sang Pe dreamer in building beauty: theme, characterization, setting, and plot. (3) The values contained in the novel The Dreamer, namely: (a) the value of social education, (b) the value of moral education, (c) the value of religious education, (d) the value of aesthetic education.Keywords: Structural Aspects, Non-structural, Novel Sang Pemimpi.